2018
DOI: 10.1186/s11671-018-2783-z
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stretchable Micro/Nano Wrinkle Structures for Infrared Stealth Application

Abstract: We demonstrate a novel infrared stealth structure consisting of SiO2/TiO2 film, which was manufactured as the highly stretchable triangular wrinkle structures. The triangular wrinkle structures have firstly been transferred to the flexible substrate from the surface of Si-substrate, which was manufactured by the MEMS technology. Then, the infrared reflective film have been manufactured to be the triangular wrinkle structures by depositing the materials (noble metal (Ag or Au) or multilayer oxide (SiO2/TiO2)) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The laser-induced wrinkled spots initiate additional wrinkles if heated further, and their interaction produces aligned patterns of wrinkles. The technique to control wrinkles reported here could find applications in functional coatings, ,, optics, ,,,, microfabrication, , stretchable electronics, and biology. , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The laser-induced wrinkled spots initiate additional wrinkles if heated further, and their interaction produces aligned patterns of wrinkles. The technique to control wrinkles reported here could find applications in functional coatings, ,, optics, ,,,, microfabrication, , stretchable electronics, and biology. , …”
Section: Discussionmentioning
confidence: 99%
“…Wrinkles can be used to determine the elastic modulus of thin films, tailor wettability by modifying surface textures, and create antifouling surfaces . Wrinkles can also be used for microlenses, flexible optical diffusers, microcircuits, and microelectromechanical systems (MEMS) . Wrinkling is also essential for flexible electronics, diffraction gratings, cell culture plates, and developmental biology …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that the stretchable wrinkle structures had a great influence on the reflection, transmission, and absorption of light, which may not be suitable for flexible displays. [ 28 ] Choi et al. reported a novel structurally and materially designed thin‐film encapsulation to protect the flexible display, in which a bioinspired, nacre‐like ZnO/Al 2 O 3 /MgO laminate structure (ZAM) was fabricated for the microcrack toughening effect.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Guo et al demonstrated that the stretchable wrinkle structures had a great influence on the reflection, transmission, and absorption of light, which may not be suitable for flexible displays. [28] Choi et al reported a novel structurally and materially designed thin-film encapsulation to protect the flexible display, in which a bioinspired, nacre-like ZnO/Al 2 O 3 /MgO laminate structure (ZAM) was fabricated for the microcrack Stretchable encapsulation plays a crucial role in expanding the applications of flexible electronics, particularly the large-area flexible displays. In this work, polydimethylsiloxane (PDMS) hybrid films with high stretchability, excellent transparency, and good barrier property are achieved by a simple process of SiO 2 doping and atomic layer infiltration (ALI).…”
mentioning
confidence: 99%